2021
DOI: 10.4239/wjd.v12.i6.893
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose response after oral lactulose intake in type 2 diabetic individuals

Abstract: BACKGROUND Lactulose is approved for the symptomatic treatment of constipation, a gastrointestinal (GI) complication common in individuals with diabetes. Lactulose products contain carbohydrate impurities ( e.g., lactose, fructose, galactose), which occur during the lactulose manufacturing process. These impurities may affect the blood glucose levels of individuals with type 2 diabetes mellitus (T2DM) using lactulose for the treatment of mild constipation. A previous stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…• Prucalopride 259 • Psyllium 260 • Flaxseed 261 • Polyethylene glycol 262 • Lactulose 263 • Lubiprostone 264 Chronic diarrhoea • Correction of fluid and electrolyte imbalances • Antidiarrhoeal agents, which inhibit intestinal peristalsis and prolong transit time while reducing faecal volume (i.e., loperamide, 265 codeine, diphenoxylate 144 ). • Bile acid-biding resins (i.e., cholestyramine, colestipol and colesevelam; limited evidence) 265 • If present, correction of associated nutritional deficiencies of folate, calcium, zinc, iron, vitamin A and magnesium • Discontinue drugs potentially interfering with intestinal function (i.e., metformin, glucagon-like peptide…”
Section: Chronic Constipationmentioning
confidence: 99%
“…• Prucalopride 259 • Psyllium 260 • Flaxseed 261 • Polyethylene glycol 262 • Lactulose 263 • Lubiprostone 264 Chronic diarrhoea • Correction of fluid and electrolyte imbalances • Antidiarrhoeal agents, which inhibit intestinal peristalsis and prolong transit time while reducing faecal volume (i.e., loperamide, 265 codeine, diphenoxylate 144 ). • Bile acid-biding resins (i.e., cholestyramine, colestipol and colesevelam; limited evidence) 265 • If present, correction of associated nutritional deficiencies of folate, calcium, zinc, iron, vitamin A and magnesium • Discontinue drugs potentially interfering with intestinal function (i.e., metformin, glucagon-like peptide…”
Section: Chronic Constipationmentioning
confidence: 99%
“…The intake of both 20 and 30 g of lactulose doses resulted in a slight net decrease in blood glucose concentrations of approx. −0.3 mmol/L from baseline as assessed by an overall negative area under the curve (AUC) of postprandial glucose response ( 18 ). Both studies showed that the oral intake of a single dose of lactulose remained largely stable in the blood glucose concentrations despite a continuous fasting period of 3 h either in healthy subjects or patients with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Lactulose given via the oral route, either as crystals, marketed as a powder to be dissolved in water, or liquid syrup containing 10 g lactulose per 15 ml solution represents the standard mode of administration for the past decades [5,8]. During the manufacturing process of these commercial lactulose preparations, some impurities, including epilactose, lactose, galactose, fructose, tagatose and small amounts of unspecified or unknown sugars can arise [7], accounting for up to 3% of total carbohydrates in crystal lactulose and approximately 30% in liquid lactulose [10]. Theoretically, these impurities could lead to an increase in blood glucose levels with a possible impact on glycemic control in individuals with DM [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…During the manufacturing process of these commercial lactulose preparations, some impurities, including epilactose, lactose, galactose, fructose, tagatose and small amounts of unspecified or unknown sugars can arise [7], accounting for up to 3% of total carbohydrates in crystal lactulose and approximately 30% in liquid lactulose [10]. Theoretically, these impurities could lead to an increase in blood glucose levels with a possible impact on glycemic control in individuals with DM [8,10]. On the other hand, the oral intake of unabsorbable disaccharides may affect carbohydrate metabolism by reducing transit time and, possibly, slowing down glucose absorption [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation